Interface Engineering via Amino Acid for Efficient and Stable Perovskite Solar Cells - Quanming Geng; Xiangrui Jia; Zhengyan He; Yanqiang Hu; Yushuang Gao; Shuo Yang; Changlin Yao; Shufang Zhang (Advanced Materials Interfaces, 2022)
Abstract In n–i–p structured perovskite solar cells (PSCs), the electron transport layer (ETL)/perovskite interfaces greatly influence the power conversion efficiency (PCE) and stability of the devices. In recent years, more and more works have successfully prepared PSCs with excellent performance after employing tin dioxide (SnO2) as ETL. However, oxygen vacancies and hydroxyl groups on the SnO2 ETLs produced during preparation can easily induce defects at the film surface and injure the above perovskite film. Herein, a multifunctional amino acid, L‐aspartic acid (LAA) is utilized, to modify the SnO2 surface and optimize the SnO2/perovskite interface. The carboxylic acid group of LAA can neutralize the alkalinity of the hydroxyl group on SnO2 film, and the amino group of LAA can interact with the perovskite layer through the hydrogen bond, to adjust the crystallization process of perovskite film. Based on the double optimization of the SnO2/perovskite interface, the defect density at the interface is greatly reduced, and the quality of the perovskite crystal is significantly improved. Finally, optimized PSCs are obtained with a high PCE of 22.63%, which is a 13% improvement over the device without LAA (20.02%). Besides, the stability performance of the PSCs modified by LAA is also remarkably improved.